Systematic review of psychometric properties of instruments measuring patient preferences for engagement in health care. (14th May 2020) - Jerofke‐Owen, Teresa; Garnier‐Villarreal, Mauricio; Fial, Alissa; Tobiano, Georgia
Abstract: Aim: To identify, critically appraise, and summarize instruments that measure patients' preferences for engagement in health care. Design: Psychometric systematic literature review. Data sources: PubMed, Embase, CINAHL, and PsycINFO were searched from inception to March 2019. Review methods: Three reviewers independently evaluated the 'methodological quality' and the 'measurement properties' of the included instruments using the Consensus‐based Standards for the Selection of Health Measurement Instruments (COSMIN) checklist and Terwee's quality criteria. Each instrument was given a Grading of Recommendations Assessment, Development and Evaluation (GRADE) score. The review was registered at PROSPERO (registry number CRD42018109253). Results: A total of 16 studies evaluating 8 instruments measuring patients' preferences for engagement in health care were included. All instruments were downgraded for their 'methodological quality' or 'measurement properties', or a combination of both. Common concerns were lack of theoretical basis, absence of patient input during development, incorrect usage and reporting of validity measures and absence of a priori hypotheses to test validity. Conclusions: There were no identified instruments that demonstrated adequate evidence for all measurement properties. The Patient Preferences for Patient Participation Scale (4Ps) and 10‐item Decisional Engagement Scale (DES‐10) had the highest overall GRADE scores; however, each had some underlying developmental or methodological issues. Impact: Assessing how patients prefer to engage in their care is a critical first step to truly individualize engagement interventions to meet patient expectations. Systematic reviews of measures of patient experience with engagement in health care have been undertaken but none are available on measures of patient preferences for engagement. The results highlight the need to further develop and test instruments that measure patients' preferences for engagement in health care within a framework for consumerism. Involving the consumer in the instrument development process will ensure that engagement strategies used by healthcare providers are relevant and individualized to consumer preferences. Abstract : 目的: 确定测量患者参与医疗保健偏好的工具, 并对其进行批判性评价和总结。 设计: 心理测量学文献系统评估。 数据来源: 通过PubMed、Embase、CINAHL和PsycINFO进行检索(从数据库建立之初到2019年3月)。 评估方法: 三名评审人员使用基于共识的健康测量工具选择标准(COSMIN)清单和Terwee的质量标准, 独立地对所纳入工具的"方法学质量"和"测量特性"进行评估。各个工具均获得了一个推荐分级的评估、制定与评价(GRADE)系统分数。本项评估已在PROSPERO进行注册(注册号:CRD42018109253)。 结果: 共纳入了16项研究, 对8种测量患者参与医疗保健偏好的工具进行了评估。所有工具均因其"方法学质量"或"测量特性"或两者组合而被降级。常见的问题包括缺乏理论基础, 在制定过程中缺乏患者输入, 有效性测量使用和报告不正确, 以及缺乏检验有效性的先验假设。 结论: 所确定的工具均不具备证明所有测量特性的充分证据。患者参与偏好量表(4Ps)和10个条目决定性参与量表(DES‐10)的GRADE得分最高;然而, 它们均存在一些潜在的制定或方法学问题。 影响: 评价患者偏好如何参与其护理是真正个性化参与干预措施以满足患者期望关键的第一步。对患者参与医疗保健体验的测量进行了系统评估, 但均不可用于患者参与偏好的测量工作。研究结果突出表明, 仍需进一步制定并检验工具, 以测量患者在消费主义框架内参与医疗保健的偏好。使消费者参与工具制定流程将可确保医疗保健提供者所采用的参与策略与消费者偏好保持相关且更加个性化。